Association of Oxidized Low-Density Lipoprotein With Prognosis of Stroke and Stroke Subtypes. Issue 1 (January 2017) - Wang, Anxin; Yang, Yuling; Su, Zhaoping; Yue, Wei; Hao, Hongjun; Ren, Lijie; Wang, Yongjun; Cao, Yibin; Wang, Yilong
Abstract : Background and Purpose—: The association between oxidized low-density lipoprotein (oxLDL) and the long-term prognosis of stroke is unclear. The aim of this study is to investigate whether oxLDL levels contribute to the prognosis of stroke and stroke subtypes. Methods—: All patients with ischemic stroke were recruited from the SOS-Stroke (Study of Oxidative Stress in Patients With Acute Ischemic Stroke) and classified into 5 different subtypes, according to the TOAST criteria (Trial of Org 10172 in Acute Stroke Treatment). We measured oxLDL levels and followed up with patients at 1 year after stroke onset. We analyzed the association between oxLDL and the clinical outcomes of death and poor functional outcome (modified Rankin Scale score of 3–6) of stroke and different stroke subtypes. Results—: Among the 3688 patients included in this study, 293 (7.94%) were deceased at the 1-year follow-up and 1020 (27.66%) had a poor functional outcome. Patients in the highest oxLDL quartile had a higher risk of 1-year stroke mortality (hazard ratio, 1.61; 95% confidence interval, 1.10–2.33; P <0.001) and a poor functional outcome (odds ratio, 1.48; 95% confidence interval, 1.15–1.89; P <0.001) compared with the lowest oxLDL quartile. In the subgroup analyses, oxLDL was only significantly associated with death and poor functional outcome in the large-artery atherosclerosis subgroup ( P <0.05) and small-artery occlusion subgroup ( P <0.05). Conclusions—: High levels of oxLDL were associated with the high risk of death and poor functional outcome within 1 year after stroke onset, especially in large-artery atherosclerosis and small-artery occlusion stroke subtypes. Abstract : Supplemental Digital Content is available in the text.